DIGITAL HUMANISM AS AN AXIOLOGICAL PARADIGM OF EDUCATIONAL TRANSFORMATION IN THE CONTEXT OF ARTIFICIAL INTELLIGENCE - Olgerd Aleksandrovich Filippov (Journals Park Publishing, 2025)
This article examines digital humanism as an axiological paradigm of educational transformation through the lens of hermeneutical and post-non-classical philosophy in the context of rapid artificial intelligence implementation. Special attention is paid to the critical analysis of contradictions between technological rationality and humanistic values, identifying risks of algorithmic bias, loss of subjectivity, and increasing educational inequality. Digital humanism is interpreted not as an external ethical superstructure but as an internal regulative for designing educational ecosystems, capable of ensuring balance between innovation and fundamental values - dignity, autonomy, critical thinking, and responsibility. The necessity of integrating value foundations into the architecture of digital platforms and pedagogical practices is emphasized, which allows resisting the technological reduction of pedagogical experience. As an original conclusion, the thesis about digital humanism as a semantic compass orienting educational systems towards the formation of subjectivity in the era of algorithms and big data is substantiated.
Keywords: Digital humanism; artificial intelligence; axiological paradigm; educational transformation; subjectivity; educational ecosystem; algorithmic bias; digitalization ethics; critical thinking; post-non-classical philosophy of education.